Analysis Of Drug Indicator At The Procurement Stage In The National Health Insurance Era: A study in Advance Health Facility - Indriyati Hadi Sulistyaningrum; Arifin Santoso; Sri Intan Lestari; Kusuma Arbianti (Universitas Muhammadiyah Magelang, 2019)
Drug procurement is part of an important hospital management to support the availability of the pharmaceutical logistic in hospital to provide good services for the patients. ineffective procurement can result in not achieving the availability of each drug in the amount which are in accordance with the price and budgeting. This research was conducted to obtain an overview of drug management at the procurement stage in Sultan Agung Islamic Hospital (RSIA SA) for the 2017 – 2018 period. Descriptive Observational research methods were used to collect the qualitative and quantitative data. Qualitative data were obtained through interview, and the quantitative data were collected from the document observation provided in Pharmaceutical installation Sultan Agung Islamic Hospital (IFRSISA). The result showed the percentage of the allocation of drug procurement funds in 2017 was 47,6%, and in 2018 it was 37,1%, the frequency of procurement of each drug type was < 76% at 12 times / year, the frequency of delayed payment by the hospital based on the time agreed was 100%. The conclusion of this study shows that the indicator of drug procurement in IFRSISA categorized as good because it is in line with the quality of drug procurement indicators.